Acute oral toxicity study of chlorhexidine lozenge in albino mice - Agdeppa, Angelica C.
This study aimed to determine safe concentrations of chlorhexidine lozenge. The researchers used four various dosages of chlorhexidine and tested its effects in albino mice by administering it orally. In order to administer it orally to the albino mice, the lozenge was prepared in a solution form and 1 ml of the solution of lozenge specifically for each group was administered orally using gavage. The solution was forced down through the animal's throats, infusing directly into the stomach. The subjects included 80 albino mice weighing 16-25 grams. The first 60 mice were divided into 2 groups of 30 mice each, wherein the first 30 were used during the exploratory phase and the second 30 were used during the confirmatory phase. During the exploratory and confirmatory phase, the 30 albino mice were again divided into 3 groups of 10 mice each per solution, wherein each group had an equal number of male and female mice., The first group was given the maximum dose of chlorhexidine lozenge (3.45g/kg), second group was given the second dose (0.345g/kg), and the third group was given the control solution, administered orally. Another 20 mice were divided into 2 groups of 10 mice each, and a confirmatory phase was done for 2 lower doses (0.0345g/kg and 0.00345g/kg) than the first two doses. Physical changes, behavioral changes and adverse effects were observed in three periods - immediately after, after 24 hours and 48 hours after the administration of the lozenge. Results showed that the four concentrations administered to the albino mice are not toxic. Furthermore at any given time point, the presence of physical, behavioral changes and adverse reaction are independent of the dose ingested to the mice. Hence, there is no significant effect of chlorhexidine lozenge in albino mice.